A Theopoetics of Mutualism: Working Toward Pneumatology in Non-Reductive Materialisms. Issue 2 (2nd April 2020) - Pryor, Adam
ABSTRACT: This article examines the significance of contemporary work on biological mutualisms for Christian theological accounts of the doctrine of the Holy Spirit. Specifically, this article evaluates the possibility of constructing a "theopoetics of mutualism, " where theopoetics marks the ongoing and creative making of God's relationship to creation, and lays the foundations for describing how the work of relating God and creation can occur within the bounds of "new materialist" accounts of agency and causality.